P172 Pre-operative insights from cardiopulmonary exercise testing in patients with pulmonary arteriovenous malformations. (15th November 2017) - Thurairatnam, S; Santhirapala, V; Hall, T; Tighe, HC; Perks, J; Jackson, JE; Howard, LS; Shovlin, CL
Abstract : Introduction and Objectives: Patients with pulmonary arteriovenous malformations (PAVMs) are difficult to assess for anaesthetic risks. Generally, they display well-preserved exercise tolerance, yet may have very low oxygen saturation due to their anatomical intrapulmonary right-to-left shunts. During pre-operative assessments in the general population, anaerobic threshold and peak VO2, measured by cardiopulmonary exercise testing (CPET), are increasingly recommended to identify high-risk patients, and appropriately plan post-operative management. For example, "high-risk" for major abdominal surgery has been suggested as an anaerobic threshold <11 ml min -1 kg -1 and peak VO2 <20 ml min -1 kg -1 . Methods: In order to evaluate "pre-operative" risk categories for PAVM patients, anaerobic threshold and peak VO2, measured by ethically approved research cardiopulmonary exercise tests, were evaluated. Results: 26 PAVM patients underwent research CPET evaluations between April 2011-May 2017. Their median age was 57 years (interquartile range (IQR): 42–66). 16 (61.5%) were male. The median oxygen saturation (SaO2 ) was 92% (IQR: 88–95) and median haemoglobin 15.6 g/dl (IQR: 14.2–16.6). Overall, the PAVM group achieved a median 92% of the predicted maximum work (IQR: 67–106), anaerobic threshold ranged from 7.6–24.5 ml min -1 kg -1 (median: 12.35; IQR: 9.5–17.35), and peak VO2 ranged from 11.2–45.5 ml min -1 kg -1 (median: 19.8; IQR: 16.7–28.4). Anaerobic threshold placed 11/26 (42.3%) in the suggested high-risk category for major abdominal surgery. In this group, the anaerobic threshold ranged from 7.6–10.8 ml min -1 kg -1 . Similarly, peak VO2 placed 14/26 (53.8%) in a high-risk category. Their peak VO2 ranged from 11.2–16.5 ml min -1 kg -1 . There was full concordance between the categories determined by the 2 measurements. Notably, 6 patients were retested 3–31 months after embolization treatment resulting in increased SaO2 . However, there was no increase in anaerobic threshold or peak VO2, and the 3 patients from this group initially in a higher risk category remained. Conclusion: Anaerobic threshold and peak VO2 suggest high proportions of PAVM patients are in a high-risk pre-operative risk category. The data suggest an important role for anaesthetic assessments. Noting that 1 in 2600 people are estimated to have PAVMs, further study is recommended to develop appropriate clinical guidance, and allocate resources to optimise care.